ANALISIS DETERMINASI MIGRASI TIDAK PERMANEN ANTAR DAERAH DI PROVINSI SUMATERA BARAT - syamsuddin, salfadri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2020)
This study aims to reveal and analyze the influence of variables of age, education level, employment status and transportation costs to the destination area to non-permanent migration between regions in the province of West Sumatra. This study uses primary data derived from surveys of people who carry out non-permanent migration between regions in West Sumatra Province. The number of samples in this study were 1040 people. This research uses multiple regression analysis. The results of this study found that the age, employment status and transportation costs to the destination area significantly influence the intermittent migration between regions in West Sumatra Province. The level of education has no significant effect on non-permanent migration between regions in West Sumatra Province.